Receptive Vocabulary of CLIL and Non-CLIL Primary and Secondary School Learners - Canga Alonso, Andrés (Complutense Journal of English Studies, 2015)
CLIL instruction has been reported to be beneficial for foreign language vocabulary learning since CLIL students show higher vocabulary profiles than students of their same age in traditional EFL contexts. However, to our knowledge, the receptive vocabulary knowledge of CLIL and non-CLIL learners at the end of primary and secondary education has not been examined yet. Hence, this study aims at comparing the receptive vocabulary size 79 CLIL primary learners with the receptive vocabulary knowledge of 331 non-CLIL learners at the end of primary and secondary school. Sex-based differences were also analysed. The 2k Vocabulary Levels Test (VLT) was used for the purposes of the study. Results revealed that learners’ receptive vocabulary sizes lie within the most frequent 1000 words, non-CLIL secondary school students throw better results than primary students but the differences between the secondary group and the CLIL group are not statistically significant. As for sex-based differences, we found no significant differences among the groups. These findings led us to believe that the CLIL approach offers a benefit for vocabulary acquisition since CLIL learners have been exposed to the foreign language for a shorter period of time and the results are quite similar to their non-CLIL secondary school partners.